MENINGKATKAN KETERAMPILAN MEMBUAT PISANG SALAI MELALUI SUMBER BELAJAR BAGI ANAK TUNAGRAHITA SEDANG KELAS VII/C (Penelitian Tindakan Kelas di SMPLB YPCC Painan) - Syafniati - T (Jurnal Penelitian Pendidikan Khusus, 2013)
The background of this research is the discovery of two moderate mental retardation students of class VII / C who have difficulty in making banana smoked during mengertjakan skills, this is because the classroom teacher can not perform deliver the subject matter in accordance with the learning steps and make banana smoked during This method only teacher demonstrations in providing eye peljaran skills, making students often forget or become less understand what the teacher explained. The purpose of this research is to improve the ability to make banana smoked through a learning resource for children mental retardation was a class VII / C. Learning resources is an environment can be used as a school teacher pebelajaran media. This pebelitian type is action research class (classroom action research) that takes the form of collaboration. These actions were taken to two children mental. Based on the average value obtained by the students at the end of the first cycle can be seen that the TN before the given action I get a value of 20% of all the indicators are given. And after a given action I got 33.33%. While the PN before the given action I get a value of 20% of all the indicators are given. After the action I was given to 25%. In the second cycle performed in four learning skills make pisnag salai, where TN got 83.33% in execution cycles II and PN also received a grade of 75%. The results of the third cycle shows the results of the ability of TN got 91.67% while the PN also scored 83.33%. banana smoked for child mental retardation was a class VII / C. Thus it can be suggested to the schools, teachers, and researchers can use the following to learning resources in improving learning skills for children tunagrahita being.